DEVELOPMENT OF GYMNASTICS IN CROATIA UP TO 1903 - Željko Iveljić; Dan Lanc; Kamenka Živčić; Lucija Milčić (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
This manuscript aimed to show the development of gymnastics in Croatia up until 1903. This article provided a chronological description of the growth of gymnastics in Croatia from 1859 to 1903. In Osijek, Croatia's first gymnastics society was founded in 1865. Gymnastics were introduced into schools in the middle of the 19th century as a result of increased interest in physical education based on by the stronger development of civil society. 1874. was founded Croatian Sokol in Zagreb and gymnastics also became a part of a high school program. In Croatia, numerous gymnastics societies started to be established, including the Varaždin Sokol Gymnastic Society in 1878 and the Zadar Gymnastic Society in 1876. In Dalmatia, central Croatia, and Slavonia, new gymnastics societies have been founded. For example, the Croatian Sokol was founded in Bjelovar in 1884 and Makarska in 1894. Additionally, the gymnastics society took part in open workouts in Prague and Pariz. Women's gymnastics started on in 1891 in Croatian Sokol in Zagreb where exercises were conducted in three divisions, including simple exercises and those on the apparatus.